The Influence of Health Education Through Tiktok Videos on the Conscious Knowledge of Adolescent Girls in Karang Langu Hamlet - Susanti, Suci Rohmi; Wahyudi, Iwan; Lita, Bq Fitria Frisma (THRIVE Health Science Journal, 2025)
Breast cancer is the most common type of cancer in women. Early detection of breast cancer can be achieved through breast selfexamination (BSE). BSE is a technique for detecting potential abnormalities in the breast that may indicate breast cancer, performed independently by individuals. This study aims to determine the effect of health education through TikTok video media on BSE knowledge before and after the intervention among adolescent girls in Karang Langu Hamlet. The method used is quantitative research with a preexperimental design, employing a one-group pre-test post-test approach. The number of respondents in this study was 48, selected using a purposive sampling technique. The results of the Wilcoxon Rank Test showed a p-value of 0.000 < 0.05, which indicates a significant influence of health education through TikTok videos on the improvement of SADARI knowledge